Exercise Type Affects Cardiac Vagal Autonomic Recovery After a Resistance Training Session. Issue 9 (September 2016) - Mayo, Xián; Iglesias-Soler, Eliseo; Fariñas-Rodríguez, Juán; Fernández-del-Olmo, Miguel; Kingsley, J. Derek
Abstract : Abstract: Mayo, X, Iglesias-Soler, E, Fariñas-Rodríguez, J, Fernández-del-Olmo, M, and Kingsley, JD. Exercise type affects cardiac vagal autonomic recovery after a resistance training session. J Strength Cond Res 30(9): 2565–2573, 2016—Resistance training sessions involving different exercises and set configurations may affect the acute cardiovascular recovery pattern. We explored the interaction between exercise type and set configuration on the postexercise cardiovagal withdrawal measured by heart rate variability and their hypotensive effect. Thirteen healthy participants (10 repetitions maximum [RM] bench press: 56 ± 10 kg; parallel squat: 91 ± 13 kg) performed 6 sessions corresponding to 2 exercises (Bench press vs. Parallel squat), 2 set configurations (Failure session vs. Interrepetition rest session), and a Control session of each exercise. Load (10RM), volume (5 sets), and rest (720 seconds) were equated between exercises and set configurations. Parallel squat produced higher reductions in cardiovagal recovery vs. Bench press ( p = 0.001). These differences were dependent on the set configuration, with lower values in Parallel squat vs. Bench press for Interrepetition rest session (1.816 ± 0.711 vs. 2.399 ± 0.739 Ln HF/IRR 2 × 10 4, p = 0.002), but not for Failure session (1.647 ± 0.904 vs. 1.808 ± 0.703 Ln HF/IRR 2 × 10 4, p > 0.05). Set configuration affected the cardiovagal recovery, with lower values in Failure session in comparison with Interrepetition rest ( p = 0.027) and Control session ( p = 0.022). Postexercise hypotension was not dependent on the exercise type ( p > 0.05) but was dependent on the set configuration, with lower values of systolic ( p = 0.004) and diastolic ( p = 0.011) blood pressure after the Failure session but not after an Interrepetition rest session in comparison with the Control session ( p > 0.05). These results suggest that the exercise type and an Interrepetition rest design could blunt the decrease of cardiac vagal activity after exercise while exercising to muscular failure may contribute to the onset of postexercise hypotension.